2012
DOI: 10.1007/s00259-012-2228-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of combined 18F-FDG PET/MRI for staging and restaging in paediatric oncology

Abstract: For the detection of single tumour lesions, registered (18)F-FDG PET/MRI proved to be the methodology of choice for adequate tumour staging. In the examination-based evaluation, MRI alone performed better than (18)F-FDG PET and combined/registered imaging during primary diagnosis. At follow-up, however, the examination-based evaluation demonstrated a superiority of (18)F-FDG PET alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…A meta-analysis by Wu et al (25) demonstrated almost equal sensitivities (;90%) of 18 F-FDG PET/CT and MR for diagnosing lymphoma with bone marrow involvement. The specificity of MR has been reported to be lower than that of 18 F-FDG PET because posttherapeutic changes, such as bone marrow edema, necrotic tissue, or age-dependent changes in the appearance of bone marrow in children, may lead to misinterpretation (25,26). A retrospective analysis of the diagnostic value of combined and coregistered 18 F-FDG PET/MR in pediatric oncology (mainly lymphoma) did not miss any bone or bone marrow lesions relative to an analysis of each modality separately.…”
Section: Lymphomamentioning
confidence: 99%
“…A meta-analysis by Wu et al (25) demonstrated almost equal sensitivities (;90%) of 18 F-FDG PET/CT and MR for diagnosing lymphoma with bone marrow involvement. The specificity of MR has been reported to be lower than that of 18 F-FDG PET because posttherapeutic changes, such as bone marrow edema, necrotic tissue, or age-dependent changes in the appearance of bone marrow in children, may lead to misinterpretation (25,26). A retrospective analysis of the diagnostic value of combined and coregistered 18 F-FDG PET/MR in pediatric oncology (mainly lymphoma) did not miss any bone or bone marrow lesions relative to an analysis of each modality separately.…”
Section: Lymphomamentioning
confidence: 99%
“…Thus, in children, PET/MRI can add significant information to that obtained through the use of separate imaging modalities. Data on the diagnostic value of combined and registered image analysis of FDG PET and MRI for staging and re-staging in pediatric oncology have recently been published [48]. On a lesionbased analysis, PET/MRI performed significantly better than the two imaging modalities alone [48].…”
Section: Whole-body Fdg Pet/mrimentioning
confidence: 99%
“…However, specificity may be limited in MRI (down to 30 %) especially in the follow-up situation (e. g., in the assessment of residual disease in Hodgkin lymphoma) [33]. In this situation, the addition of PET can significantly increase diagnostic sensitivity (up to 97 %) and specificity (up to 82 %) by combination of high anatomic resolution and high sensitivity of MRI and complementary metabolic information of PET [33]. It is thus self-evident that combined PET/MRI is indicated in patients with indications for whole-body MRI and PET.…”
mentioning
confidence: 99%
“…Whole-body MRI is the method of choice for imaging of numerous oncologic disorders in children, especially for primary diagnosis and staging [30 -32]. For this purpose, MRI provides high sensitivity for lesion detection and excellent soft-tissue contrast for local staging (up to 94 %) [16,33]. However, specificity may be limited in MRI (down to 30 %) especially in the follow-up situation (e. g., in the assessment of residual disease in Hodgkin lymphoma) [33].…”
mentioning
confidence: 99%
See 1 more Smart Citation